146k views
1 vote
Which of the following is the simplified form of fifth root of x times the fifth root of x times the fifth root of x times the fifth root of x?

User KristiLuna
by
5.3k points

2 Answers

2 votes

Answer:

x^4/5

Explanation:

User Laerte
by
5.0k points
5 votes

Answer:

Simplified form of fifth root of x times the fifth root of x times the fifth root of x times the fifth root of x is
\sqrt[5]{x^(4)}

Solution:

Need to find simplified form of fifth root of x times the fifth root of x times the fifth root of x times the fifth root of x. That is need to find simplified form of following expression.


\sqrt[5]{x} * \sqrt[5]{x} * \sqrt[5]{x} * \sqrt[5]{x}


\text { since } \sqrt[n]{a}=(a)^{(1)/(n)} we get


=>(x)^{(1)/(5)} *(x)^{(1)/(5)} *(x)^{(1)/(5)} *(x)^{(1)/(5)}

Now using law of exponent that is
\mathrm{a}^{\mathrm{m}} * \mathrm{a}^{\mathrm{n}}=\mathrm{a}^{\mathrm{m}+\mathrm{n}}


\begin{array}{l}{\Rightarrow(x)^{(1)/(5)} *(x)^{(1)/(5)} *(x)^{(1)/(5)} *(x)^{(1)/(5)}} \\\\ {=(x)^{(1)/(5)+(1)/(5)} *(x)^{(1)/(5)}} \\\\ {=(x)^{(2)/(5)} *(x)^{(2)/(5)}} \\\\ {=(x)^{(2)/(5)} *(x)^{(2)/(5)}} \\\\ {=(x)^{(2)/(5) +(2)/(5) \\\\ {=(x)^{(4)/(5)}}\end{array}

Using another law of exponent that is
(a)^(m * n)=\left((a)^(m)\right)^(n) we get


\begin{array}{l}{(x)^{(4)/(5)}=(x)^{4 * (1)/(5)}=\left((x)^(4)\right)^{(1)/(5)}} \\\\ {\left((x)^(4)\right)^{(1)/(5)}=\sqrt[5]{x^(4)}}\end{array}

Hence the simplified form of fifth root of x times the fifth root of x times the fifth root of x times the fifth root of x is
\sqrt[5]{x^(4)}

User Janne Enberg
by
5.5k points